2021
DOI: 10.20945/2359-3997000000417
|View full text |Cite
|
Sign up to set email alerts
|

The rs2442598 polymorphism in the ANGPT-2 gene is associated with risk for diabetic retinopathy in patients with type 1 diabetes mellitus in a Brazilian population

Abstract: Objective: As studies have reported the involvement of angiopoietin-2 (ANGPT-2) in the pathogenesis of diabetic retinopathy (DR), the aim of this study was to investigate the association between the ANGPT-2 rs2442598 polymorphism and DR. Materials and methods: This case-control study comprised 107 patients with type 1 diabetes mellitus (T1DM) and DR (cases) and 129 patients with T1DM without DR (controls) and with ≥ 10 years of DM. The ANGPT-2 rs2442598 (G/A) polymorphism was genotyped by real-time PCR using T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
1
1
0
1
Order By: Relevance
“…These findings are consistent with studies in patients with sepsis where an Angpt-2 gene variant (rs2920656C > T) associated with lower Angpt-2 protein levels was associated with a less severe sub-phenotypes of AKI [9]. Perturbations in the Angpt-Tie-2 pathway have been implicated in multiple forms of retinopathy [10,11] and polymorphisms in the ANGPT2 gene have also been implicated in retinopathy (rs2442598 G>A) [12]. Based on these findings, there is a strong reason to believe that malaria will impact choroidal thickness in children, as proposed by Burke et al, and studies should investigate the relationship between the Angpt-2-Tie-2 axis as it relates to the kidney, brain, and retina.…”
supporting
confidence: 88%
“…These findings are consistent with studies in patients with sepsis where an Angpt-2 gene variant (rs2920656C > T) associated with lower Angpt-2 protein levels was associated with a less severe sub-phenotypes of AKI [9]. Perturbations in the Angpt-Tie-2 pathway have been implicated in multiple forms of retinopathy [10,11] and polymorphisms in the ANGPT2 gene have also been implicated in retinopathy (rs2442598 G>A) [12]. Based on these findings, there is a strong reason to believe that malaria will impact choroidal thickness in children, as proposed by Burke et al, and studies should investigate the relationship between the Angpt-2-Tie-2 axis as it relates to the kidney, brain, and retina.…”
supporting
confidence: 88%
“…The rs2442598A allele in the ANGPT-2 gene is associated with an increased risk for diabetic retinopathy in Brazilian patients with type 1 DM [165]. Intravitreal levels of Ang2 are also elevated in eyes with DME and PDR [166][167][168]. A recent systematic review and meta-analysis reported that intravitreal levels of Ang2 are elevated in eyes with PDR when compared to healthy non-diabetic eyes [169].…”
Section: Diabetic Patients and Ang-tie Signalingmentioning
confidence: 99%
“…) con RD, se encontró que tampoco hay una asociación de estos con RD 20 . Además, se analizaron polimorfismos del gen ANGPT-2 (SNP rs2442598); los autores encontraron que en pacientes con diabetes tipo 1 había una asociación entre el genotipo A/A y el alelo A con la susceptibilidad de padecer RD, y se encontraba con mayor frecuencia en pacientes que presentaban la complicación 21 . También, en diabetes tipo 1, se analizaron polimorfismos del gen ERBB3 (rs705708 alelo A) y su regulador PA2G4 (rs773120), que son polimorfismos que se han estudiado por su aparente relación con el riesgo para padecer diabetes tipo 1.…”
Section: Mexicana Sin Especificar Etniaunclassified